Last house : or, the age of oil [large type] - Shattuck, Jessica (Harper Large Print, an imprint of HarperCollins Publishers, 2024)
"Spanning multiple generations and nearly 80 years, this emotional tour de force follows one American family, during the radical movement of the 1968 against Big Oil, as they are forced to reckon with the consequences of the resources that built their fortune and fueled their greatest tragedy"--